Single-step synthesis of 4-phenyl and 3,4-dihydro-4-phenyl coumarins using a recyclable Preyssler heteropolyacid catalyst under solvent-free reaction conditions - Escobar Caicedo, Angélica María (2015)
4-Phenyl and 3,4-dihydro-4-phenylcoumarins were prepared by direct esterification of phenols with phenylpropiolic and cinnamic acids, respectively, using a compound with Preyssler structure (H14P5NaW30O110) (PA) as heterogeneous catalyst under solvent-free reaction conditions, at 130 C, in a short reaction time (2 h). Underthese conditions, very good yields (11 examples: 61 %–90 %), free of secondary products, were obtained. The catalyst is recyclable, nontoxic, neither air nor moisture sensitive, and easy to handle. The described methodology is a clean and useful alternative to synthesize oxygenated heterocycles based on a coumarin skeleton.